Famous Works of Art-- And How They Got That Way - Nici, John B. (Rowman & Littlefield, 2015)
"In a world filled with great museums and great paintings, Leonardo da Vinci's Mona Lisa is the reigning queen. Her portrait rules over a carefully designed salon, one that was made especially for her in a museum that may seem intended for no other purpose than to showcase her virtues. What has made this portrait so renowned, commanding such adoration? And what of other works of art that continue to enthrall spectators: What makes the Great Sphinx so great? Why do iterations of The Scream and American Gothic permeate nearly all aspects of popular culture? Is it because of the mastery of the artists who created them? Or can something else account for their popularity? In [this book, the author] looks at twenty well-known paintings, sculptures, and photographs that have left lasting impressions on the general public. As Nici notes, there are many reasons why works of art become famous; few have anything to do with quality. The author explains why the reputations of some creations have grown over the years, some disproportionate to their artistic value. Written in a style that is both entertaining and informative, this book explains how fame is achieved, and ultimately how a work either retains that fame, or passes from the public consciousness. From ancient artifacts to a can of soup, this book raises the question: Did the talent to promote and publicize a work exceed the skills employed to create that object of worship? Or are some masterpieces truly worth the admiration they receive? The creations covered in this book include the Tomb of Tutankhamun, Botticelli's Birth of Venus, Raphael's Sistine Madonna, El Greco's The Burial of Count Orgaz, Rodin's The Thinker, Van Gogh's Starry Night, and Picasso's Guernica. Featuring more than sixty images, including color reproductions, [this book] will appeal to anyone who has ever wondered if a great painting, sculpture, or photograph, really deserves to be called 'great'"--Amazon.com.